Keabsahan Kesepakatan Bersama Antara Operator Arung Jeram dengan Masyarakat Desa Bartong Kecamatan Sipispis Ditinjau dari Syarat Sah Perjanjian - Arum Valenthia, Tirta; Faisal, Faisal (UNES Law Review, 2024)
This study aims to determine whether the agreement between the Rafting Operator and the Bartong Village community is valid according to the law when viewed from the valid terms of the agreement. This research uses empirical research, namely research with field data as the main data source, such as the results of interviews and observations. The results of the study found that the mutual agreement between the Rafting Operator and the Bartong Village community has fulfilled the four elements of the valid terms of the agreement regulated in Article 1320 of the Civil Code. The Bartong Village community agreed and agreed that the Rafting activity could use Huta Bayu Village in Bartong Village as a starting point location with agreed operational costs. The parties present and involved in the agreement can be ascertained that they are capable according to the law. The rafting activity does not disturb public order and decency, nor does it violate the law. So the joint agreement between the Rafting Operator and the Bartong Village community can be declared valid in terms of the validity of the agreement.